Does Financial Technology Improve Health in Asian Economies? - Jing, Ran; Ma, Yechi; Zhang, Liangyu; Hafeez, Muhammad (Frontiers in Public Health, 2022)
The progress of the health sector in a sustainable manner is crucial for the development of human capital, a significant and vital driver of economic growth. Hence, we aim to investigate the impact of Fintech on health outcomes in Asian economies over the period 2007-2019. The empirical estimation of the study is based on the 2SLS and GMM techniques. The outcomes confirmed the negative impact of ATMs and Debit cards on the infant mortality rate in both 2SLS and GMM models. Whereas ATMs and Debit cards positively impact the life expectancy of people living in Asian economies irrespective of the estimation technique. Similarly, the association between the Internet and infant mortality rate is negative; whereas, this association is positive in the context of the Internet and life expectancy both with 2SLS and GMM. From these findings, we can confirm that the amalgamation of technology and the financial sector helps to improve health outcomes in Asian economies. Therefore, the integration of Fintech into the health sector should be part and parcel of every health policy in emerging Asian economies.